Saligia - Strydom, Gideon Louwrens (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
When her life starts falling apart, a journalist and writer heads for a small rural town. Here the strange and wonderful tales about a local woman ignite her curiosity. As the town's secrets unravel she finds the truth behind all the fantasies. And in fighting her own demons she makes an unusual connection to this woman. She soon realises that this connection holds the key to her own salvation. Or her downfall.
Keywords: Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Fiction; Afrikaans fiction -- Study and teaching (Higher); Afrikaans fiction -- 21st century